Expelled
WITNESS, Columbia University Human Rights Law Clinic and the National Coalition for Haitian Rights teamed up to produce EXPELLED, a video that documents the Dominican Government's practice of illegal expulsions of people of Haitian descent who live in the Dominican Republic. In March 2001, the video was screened before the UN Human Rights Committee.